Macro-Scale Complex Form Generation Through a Swarm Intelligence-Based Model with Urban Morphology Constants - Agirbas, Asli (Taylor & Francis Ltd, 2020)
Designing through the use of complex forms is becoming increasingly widespread. However, when designing macro-scale projects with complex forms, urban constants should be included in the design process. In this study, to begin, urban morphology constants were identified through a literature survey, which revealed constants such as road networks and topography. Next, a swarm intelligence-based model that included urban morphology constants in the swarm algorithm as constraints was developed. Development of this model entailed the use of a visual programming language. Conceptual forms produced as a result of swarm simulation were evaluated through a case study on a section of the Italian city of Genoa.
Keywords: Urban Morphology Constants; Swarm Intelligence; Multi-Agent Systems; Conceptual Design; Macro-Scale Design; Complex Forms